Toxic Potential and Metabolic Profiling of Two Australian Biotypes of the Invasive Plant Parthenium Weed (Parthenium hysterophorus L.) - Ali Ahsan Bajwa; Paul A. Weston; Saliya Gurusinghe; Sajid Latif; Steve W. Adkins; Leslie A. Weston (Toxins, 2020)
Parthenium weed (Parthenium hysterophorus L.) is an invasive plant species in around 50 countries and a ‘Weed of National Significance’ in Australia. This study investigated the relative toxicity of the leaf, shoot and root extracts of two geographically separate and morphologically distinct biotypes of parthenium weed in Queensland, Australia. Parthenium weed exhibited higher phytotoxic, cytotoxic and photocytotoxic activity in leaf tissue extracts in contrast to shoot and root. The germination and seedling growth of a dicot species (garden cress) were inhibited more than those of a monocot species (annual ryegrass) using a phytotoxicity bioassay. The cytotoxicity of leaf extracts was assessed in a mouse fibroblast cell suspension assay and increased under high ultraviolet A(UV-A) radiation. A major secondary metabolite, parthenin, was found in abundance in leaf extracts and was positively correlated with cytotoxicity but not with photocytotoxicity or phytotoxicity. Ambrosin and chlorogenic acid were also detected and were positively correlated with germination inhibition and the inhibition of radicle elongation, respectively. In addition, other currently unidentified compounds in the leaf extracts were positively correlated with phytotoxicity, cytotoxicity and photocytotoxicity with two to three molecules strongly correlated in each case. Both parthenium weed biotypes investigated did not differ with respect to their relative toxicity, despite their reported differences in invasive potential in the field. This suggests that secondary chemistry plays a limited role in their invasion success.